Empowering Teachers’ Commitment: How Do Six Dimensions of Sustainable Leadership Play A Role? Memperkasakan Komitmen Guru: Bagaimanakah Enam Dimensi dalam Kepimpinan Lestari Memainkan Peranan? - How, Richeal Phil Thien Kim; Ishak, Mohd Zaki (Management Research Journal, 2021)
This study was conducted to examine the relationship between the six dimensions of sustainable leadership practices by principals with the level of commitment by secondary school teachers. The sample comprised 269 respondents who were school administrators including senior assistants, Heads of Departments, and secretaries from 8 secondary schools in the district of Lahad Datu. The researchers adapted a modified instrument based on the Sustainable Leadership Model while the Organisational Commitment Questionnaire was used to identify the level of teachers’ commitment. A pilot study was conducted and the Cronbach’s Alpha value indicated high consistency among the items in the questionnaire. Descriptive analysis was then conducted to determine the frequency of sustainable leadership dimensions practised by the principals. Inferential analysis of Pearson Correlation was also conducted to test the hypotheses. The results showed that teachers perceive principals’ sustainable leadership practices to be at a moderately high level. Furthermore, the six dimensions of sustainable leadership had a positive and significant relationship with the level of teachers’ commitment. These findings contribute to the development of sustainable leadership theory and organisational commitment within the educational environment. This suggests that significant attention should be placed on the aspect of sustainable leadership to increase the level of teachers’ commitment. The study also highlights the importance for principals to adopt a sustainable leadership style in administering and managing their schools so that the commitment of teachers can be enhanced and further achieve the vision and mission of the schools.